Sistem Aplikasi Penggadaian Berbasis Destop Menggunakan Visual Studio.Net - Jimmy Nganta Ginting (Universitas Budi Darma, 2024)
Pawnshop is a form of non-bank financial institution that has activities to finance the needs of the community. Pegadaian is currently starting to move towards the stage of transformation into a financial company, the change made by this company by creating an application to make it easier for customers to transact. This research aims to design a pawnshop Digital Service application to make it easier for customers to transact at ummar pawn pawnshops. This study uses a qualitative method with a descriptive approach and is analyzed by interviewing pawnshop employees, as well as from pawnshop customers. So with this, PT. Penggadaian , hopes that in the future it will continue to maintain relationships with customers to maintain cooperation, so that it will increase even more in the future, in addition to attracting people to become customers. This pawn application is designed using visual basic software and the database uses access, with this pawn application, it not only helps customers, but also helps admins at PT. Penggadaian in the preparation of pawn evidence and preparation of pawn reports